Life in the key of G - G., Kenny; Lerman, Philip (Blackstone Publishing, 2024)
"In this heartfelt, funny, and fascinating memoir, Kenny G shares how skinny Kenneth Gorelick, the kid who got hassled for his lunch money in a Seattle high school, became one of the most celebrated and revered virtuosos in the music industry. He uncovers how he's managed to rise above the fray, tune out the critics, and live a life filled with happiness and humor"--